An assessment of adequate quality antenatal care and its determinants in India - Saif Nihal; Chander Shekhar (BMC, 2024)
Abstract Background Antenatal care (ANC) is an important component in the continuum of care. Providing adequate quality ANC is necessary to prevent maternal and newborn mortality. The coverage of ANC has increased significantly in the last decade in India, but a mere increase in coverage is insufficient if the issue of quality is not simultaneously addressed. This study examines the change in each component of quality ANC between 2015-16 and 2019-21, highlights the factors associated with adequate quality ANC, and observes the state- and district-level distribution of adequate quality ANC during 2019-21. Methods This study is based on data from the two most recent rounds of the National Family Health Survey (NFHS), the Indian equivalent of the Demographic and Health Surveys (DHS). These rounds were conducted in 2015-16 and 2019-21 in selected households of India with a total of 190,797 and 176,843 sampled births, respectively. The dependent variable was quality antenatal care, a composite variable consisting of skilled healthcare providers, timeliness, sufficiency, and appropriateness of content. The independent variables were mother's age, education, wealth quintile, birth order, mass media exposure, health insurance coverage, relationship with the head of household, facility exposure, intended pregnancy, history of adverse pregnancy outcomes, and other socio-demographic variables. Change in each component and dimension of quality antenatal care was assessed using data from both rounds of the survey. A multivariate multinomial logistic regression analysis was employed to identify the determinants of adequate quality ANC using the NFHS-5 data. Results The findings revealed that 32 per cent of mothers received adequate quality antenatal care in 2019-2021, an increase of only 9% points compared to the 2015-16 period. Two significant barriers to achieving adequate quality antenatal care, in terms of appropriateness of content, were the provision of Iron and Folic Acid (IFA) tablets and counselling. The highest utilisation of adequate quality antenatal care was observed in the southern states. The utilisation of quality ANC increased with an increase in women's education and wealth status; and was more prevalent among those with health insurance coverage and exposure to mass media. Conclusion Despite some improvements in the coverage of antenatal care, the quality of antenatal care continues to be very low and needs urgent attention. Achieving quality antenatal care in both content and experience requires addressing service gaps and developing better measures to capture and improve women's care experiences.